2019
DOI: 10.1101/799312
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-resolution micro-epidemiology of parasite spatial and temporal dynamics in a high malaria transmission setting in Kenya

Abstract: 1 2 3 High-resolution micro-epidemiology of parasite spatial and temporal dynamics in a high 4 malaria transmission setting in Kenya 5 6 7 Cody S. Abstract WC: 149 (150 max) 24Main Text WC: 4,830 (5,000 max) 25Methods WC: 2,450 (3,000 max) 26 ABSTRACT 27Novel interventions that leverage the heterogeneity of parasite transmission are needed to push 28 malaria further towards elimination. To better understand spatial and temporal dynamics of 29 transmission, we applied amplicon NGS of two polymorphic gene region… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Of interest to those working on malaria surveillance in high-transmission areas is whether measuring MOI, and in turn population size, using var repertoires or single copy antigen genes or by neutral variation with biallelic SNPs, is more relevant to the elimination agenda in high burden countries. Single copy antigen genes such as csp, msp2, and ama1 have each been used to measure MOI (e.g., (Falk et al, 2006;Lerch et al, 2017;Nelson et al, 2019)) and have become part of newer genetic panels (e.g., Paragon v1 (Tessema et al, 2020) andAMPLseq v1 (LaVerriere et al, 2022)). These genes are under balancing selection with geographically common alleles.…”
Section: Resultsmentioning
confidence: 99%
“…Of interest to those working on malaria surveillance in high-transmission areas is whether measuring MOI, and in turn population size, using var repertoires or single copy antigen genes or by neutral variation with biallelic SNPs, is more relevant to the elimination agenda in high burden countries. Single copy antigen genes such as csp, msp2, and ama1 have each been used to measure MOI (e.g., (Falk et al, 2006;Lerch et al, 2017;Nelson et al, 2019)) and have become part of newer genetic panels (e.g., Paragon v1 (Tessema et al, 2020) andAMPLseq v1 (LaVerriere et al, 2022)). These genes are under balancing selection with geographically common alleles.…”
Section: Resultsmentioning
confidence: 99%
“…We evaluated COI estimation based on 4CAST as opposed to the single locus AMA1 , which is commonly used for this purpose, alone or together with a single additional locus (Lerch et al, 2017; Miller et al, 2017; Nelson et al, 2019). We engineered in silico samples with COI ranging from 2 to 10 (100 engineered samples per COI level) and used the maximum number of unique microhaplotypes present at any locus as a simple data summary method to estimate COI.…”
Section: Resultsmentioning
confidence: 99%
“…(29) A recent study that employed targeted amplicon deep sequencing to genotype parasites found that symptomatic children more commonly shared haplotypes with asymptomatically infected household members; however, household members were not strati ed by age in this study. (25) Understanding more about household clustering of infections, including the dynamics of within-household transmission, would be helpful in determining whether malaria control interventions aimed at disrupting transmission within households are worth pursuing.…”
Section: Discussionmentioning
confidence: 99%
“…Other genotyping techniques that are able to resolve multiallelic loci, such as multiplex amplicon or "microhaplotype" sequencing, can provide rich data from polyclonal infections and leverage current sequencing technologies to more easily allow evaluation of larger numbers of loci, providing higher resolution to evaluate transmission particularly in moderate-high transmission settings. (25,(31)(32)(33)(34) While these methods are more expensive and require more extensive laboratory and bioinformatics structure than the methods used in this study, they may be preferred techniques in the future as sequencing costs continue to decline.…”
Section: Discussionmentioning
confidence: 99%